Investment Interest of Young Generation in The Sriwijaya State Polytechnic: : Theory of Planned Behavior Approach - Ulfah Muharramah; Yesita Astarina; Dwi Riana; Heri Setiawan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2023)
Purpose –This study wants to examine the factors that can influence the interest of the younger generation to invest in the Sriwijaya State Polytechnic through the Theory of Planned Behavior (TPB) approach.Methodology–This study uses a quantitative approach. Samples were taken using the Non Probability Sampling technique with purposive sampling method. The sample used in this study was 164 respondents. The multiple linear regression model was used in this study by utilizing the SPSS statistical data processing program. The results of this study indicate that financial literacy has an effect on the investment interest of the younger generation (millennials and gen Z), while financial efficacy and perceived risk have no effect on the investment interest of the younger generation. Financial literacy is proven to encourage interest in investing, especially in the capital market. This proves that if someone has good knowledge and understanding of finance, it will certainly generate interest or intention to act on financial management. Meanwhile, financial efficacy and perceived risk are not able to encourage someone's interest to invest. Novelty/values –These findings indicate that the younger generation has different attitudes and views when faced with the decision to invest.